1996
DOI: 10.1097/00005344-199605000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Reperfusion-Induced Arrhythmias by Human Thioredoxin

Abstract: Adult T-cell leukemia-derived factor (ADF), identified in the supernatant of adult T-cell leukemia (ATL) cell culture, is a human homologue of thioredoxin and consists of 104 amino acids; it has two redox-active half-cysteine residues in an exposed active center. Human thioredoxin has many biological activities, including growth promotion, cell activation, and a catalase-like radical scavenging activity. We examined the protective effect of human thioredoxin (h-thioredoxin) against reperfusion-induced arrhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Several studies, for example, have already reported that injection of a bolus of Trx substantially prevents ischemic reperfusion injury (15)(16)(17)(18). These findings were previously ascribed to the reducing power of Trx and its ability to remove locally generated reactive oxygen intermediates.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies, for example, have already reported that injection of a bolus of Trx substantially prevents ischemic reperfusion injury (15)(16)(17)(18). These findings were previously ascribed to the reducing power of Trx and its ability to remove locally generated reactive oxygen intermediates.…”
Section: Discussionmentioning
confidence: 97%
“…It is induced by oxidative stress (8,11), is translocated into the nucleus in stressed cells (8,11), is chemotactic in vitro for eosinophils (7), and effectively blocks ischemic injury (15)(16)(17)(18). In addition, our recent studies show that Trx has potent in vitro and in vivo chemoattractant activity for murine neutrophils, monocytes, and lymphocytes (9).…”
mentioning
confidence: 99%
“…On the basis of the identification of TrxR1-mediated control of growth factor signaling, it will be highly interesting to investigate whether alterations in TrxR1 levels or activity, as observed for example in an animal model of liver cancer (54) and arrhythmia (63), are associated with etiologically relevant alterations in growth factor and receptor tyrosine kinase signaling.…”
Section: Discussionmentioning
confidence: 99%
“…27 TRX expression is upregulated during the acute stage in rats with giant cell myocarditis, and the development of acute immune-mediated myocarditis may be regulated by the cellular redox state via TRX. 28 Recombinant TRX protected against reperfusion injury in an ischemic lung model 29 and against reperfusion-induced arrhythmias in an isolated rat heart model, 4 and overexpression of TRX in transgenic mice attenuated focal ischemic brain damage. 15 Taken together, these data indicate that TRX protects organs from the cytotoxicity caused by ROS.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Moreover, TRX eliminates hydrogen peroxide and acts as a radical scavenger, and recombinant TRX has a protective activity against hydrogen peroxide cytotoxicity, in which the generation of ROS seems to be involved. 14,16 TRX suppressed reperfusion-induced arrhythmias in an isolated rat heart model, 4 and overexpression of TRX in transgenic mice was protective for postischemic reperfusion injury in the brain in vivo. 17 However, the levels of TRX that regulate the cellular redox state have not been investigated in human patients with heart diseases.…”
mentioning
confidence: 92%